PENGARUH KEGIATAN KEPRAMUKAAN TERHADAP AKHLAK SANTRI DAN SANTRIWATI PONDOK PESANTREN ADLANIYAH DI JORONG TAMPUS KECAMATAN LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Ummul Aini; Deswalantri Deswalantri; Alimir Alimir; Jasmienti Jasmienti (Universitas Pahlawan Tuanku Tambusai, 2022)
Morals are rules that come from religion which do not only regulate the outward but also the mind and the mind and regulate good relations with fellow human beings, with God, with animals, plants, and inanimate objects even though they are also contained in morals. The problem in this study is that there are still many students and female students who do not respect the scout supervisor explaining the material, lying, arrogant, isolating friends, littering, and not helping friends who are having difficulties. The purpose of this study was to find out how much Scouting Activities provide The influence on the morals of students and students at the Adlaniyah Islamic Boarding School in Jorong Tampus, Lembah Melintang District, West Pasaman Regency. This type of research is a quantitative research with a descriptive approach. The population in this study were all students and female students who took part in scouting activities for the 2021/2022 academic year, totaling 266 students and female students. And for the number of samples in this study amounted to 50 students and students who were taken using proportional stratified random sampling as sampling. The data in this study were taken by the questionnaire method. The method of data management or data analysis in this study uses the Simple Linear Regression formula. Based on the results of the correlation coefficient analysis, Scouting activities have quite an influence on the Morals of Santri and Santriwati. And based on the results of the analysis of the Hypothesis Test, it was found that Scouting Activities had a positive and significant effect on the Morals of Santri and Santriwati. This can also be seen from the calculation results of the Coefficient of Determination, the value of R^2 is 0.199 or 19.9%. This means that Scouting activities have an influence on the Morals of Santri and Santriwati by 19.9% ​​and the rest is influenced by other variables not examined. Keywords: scouting activities, influence, morality